Evil thing : a Villains graphic novel - Valentino, Serena (Valentino, Serena. Villains graphic novel., 2021)
"This graphic novel adaptation of Serena Valentino's Villains series follows the rise and fall of the deranged and glamorous fan favorite, Cruella De Vil. If it doesn't scare you, no evil thing will.."--